Interventional Oncology in Hepatocellular Carcinoma: Progress Through Innovation. Issue 6 (November 2016) - Mu, Lin; Chapiro, Julius; Stringam, Jeremiah; Geschwind, Jean-François
Abstract : Abstract: The clinical management of hepatocellular carcinoma has evolved greatly in the last decade mostly through recent technical innovations. In particular, the application of cutting-edge image guidance has led to minimally invasive solutions for complex clinical problems and rapid advances in the field of interventional oncology. Many image-guided therapies, such as transarterial chemoembolization and radiofrequency ablation, have meanwhile been fully integrated into interdisciplinary clinical practice, whereas others are currently being investigated. This review summarizes and evaluates the most relevant completed and ongoing clinical trials, provides a synopsis of recent innovations in the field of intraprocedural imaging and tumor response assessment, and offers an outlook on new technologies, such as radiopaque embolic materials. In addition, combination therapies consisting of locoregional therapies and systemic molecular targeted agents (e.g., sorafenib) remain of major interest to the field and are also discussed. Finally, we address the many substantial advances in immune response pathways that have been related to the systemic effects of locoregional therapies. Knowledge of these new developments is crucial as they continue to shape the future of cancer treatment, further establishing interventional oncology along with surgical, medical, and radiation oncology as the fourth pillar of cancer care.